Characterizing Mobilized Virulence Factors and Multidrug Resistance Genes in Carbapenemase-Producing Klebsiella pneumoniae in a Sri Lankan Hospital - Zhu, Chendi; Liyanapathirana, Veranja; Li, Carmen; Pinto, Vasanthi; Hui, Mamie; Lo, Norman; Wong, Kam T.; Dissanayake, Nilanthi; Ip, Margaret (Frontiers in Microbiology, 2018)
Limited data is available on the epidemiology and characteristics of carbapenem-resistant Enterobacteriaceae (CRE) and their associated plasmids or virulence determinants from Sri Lanka. Through whole genome sequencing of CREs from the intensive care units of a Sri Lankan teaching hospital, we identified a carbapenemase gene, blaOXA–181 in 10 carbapenemase-producing Klebsiella pneumoniae isolates (two strains of ST437 and eight strains of ST147) from 379 respiratory specimens. blaOXA–181 was carried in three variants of ColE-type plasmids. K. pneumoniae strains with ompK36 variants showed high minimum inhibitory concentrations to carbapenem. Furthermore, genes encoding for extended spectrum β-lactamases (ESBL), plasmid-mediated quinolone resistance (PMQR) determinants (qnr, aac(6′)-Ib-cr, and oqxAB) were present in all 10 strains. Amino acid substitution in chromosomal quinolone resistance-determining regions (QRDRs) gyrA (Ser83Ile) and parC (Ser80Ile) were also observed. All strains had yersiniabactin genes on mobile element ICEkp. Strict infection control practices and judicious use of antibiotics are warranted to prevent further spread of multidrug-resistant K. pneumoniae.